2019
DOI: 10.24036/00173za0002
|View full text |Cite
|
Sign up to set email alerts
|

Improving Discipline Analysis of High School Students with Guidance and Counseling approaches

Abstract: Discipline is defined as the compliance with existing rules or regulations with pleasure and self-awareness. It has a huge influence on learning, personal interest, social life and career of students. Therefore, the purpose of this study is to describe the disciplinary problems of students at SMAN 2 Padang and ways to improve it using the right counseling approach. Data was analyzed using the quantitative and descriptive methods with a reliability scale of 0.909. The research findings shows the discipline of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Second, research conducted by (Husain, 2016), the results of the research that the authors examined showed that the strategy of the Islamic Religious Education teacher in overcoming the learning boredom of elementary school children was carried out by providing spiritual guidance, joking, and telling stories. Third, in research conducted by (Agustina, 2019), in his research, the researcher emphasized that counseling and religious strategies in the efforts of teachers to overcome boredom in student learning were lecturing and giving motivation.…”
Section: Introductionmentioning
confidence: 99%
“…Second, research conducted by (Husain, 2016), the results of the research that the authors examined showed that the strategy of the Islamic Religious Education teacher in overcoming the learning boredom of elementary school children was carried out by providing spiritual guidance, joking, and telling stories. Third, in research conducted by (Agustina, 2019), in his research, the researcher emphasized that counseling and religious strategies in the efforts of teachers to overcome boredom in student learning were lecturing and giving motivation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, 10 percent reported acts of student disrespect on teachers other than verbal abuse, 2 percent analyzed widespread disorder in the classroom and student racial/ethnic tensions, and 1percent each reported sexual harassment of other studentsbased on sexual orientation or gender identity. Finally, 10 percent of public schools reported that gang activities occurred during the 2015-16 school year (Gustiana et al, 2020). However, not all students are disciplinewhich leads to problems such as disruptive classroom behaviour, vandalism, bullying, and violence (Luiselli et al, 2005).…”
Section: Introductionmentioning
confidence: 99%